Investigation on Low-temperature Annealing Process of Solution-processed TiO2 Electron Transport Layer for Flexible Perovskite Solar Cell - Yu, Xing; Zou, Xiaoping; Cheng, Jin; Chen, Dan; Yao, Yujun; Chang, Chuangchuang; Liu, Baoyu; Wang, Junqi; Zhou, Zixiao; Li, Guangdong (Materials, 2020)
Flexible perovskite solar cells (PSCs) have received increasing attention in wearable and portable devices over the past ten years. The low-temperature process of electron transport layer plays a key role in fabricating flexible PSCs. In this paper, we improve the performance of flexible PSCs by controlling the thermodynamic procedure in the low-temperature annealing process of solution-processed TiO2 layers and modulating the precursor concentration of (6,6)-phenyl c61 butyric acid methyl ester (PC61BM) deposited on fluorine-doped tin oxide (FTO)/TiO2 substrate. The results show that slowing down evaporation rate of residual solvent and adopting PC61BM of appropriate precursor concentration are confirmed to be effective methods to improve the performance of flexible PSCs. We also demonstrate carbon electrode-based flexible PSCs. Our work expands the feasibility of low temperature process for the development of flexible perovskite photodetectors and light-emitting diodes, as well as flexible PSCs.